HUBUNGAN JOB DEMAND, DUKUNGAN ORGANISASI, DAN KARAKTERISTIK PEKERJA TERHADAP KEJADIAN BURNOUT PADA PEKERJA PRODUKSI PT X TAHUN 2023 - Nur Afifah Fajriyah (2024)
Many cases of burnout have been found in various fields of work, including PT X which operates in the manufacturing sector. PT X production workers were found symptoms of burnout. Factors causing burnout are classified into two, individual and organizational factors. The study aims to determine the relationship between job demands, organizational support, and worker characteristics on the incidence of burnout in PT X production workers. The study was a quantitative research with cross-sectional design. Populations were all production unit workers at PT X with 117 sample of workers using a simple random sampling technique. Data collection were carried out by distributed questionnaires filled in directly by respondents. Data analysis were bivariate using the chi-square test. The study results showed that 51.3% of PT X production workers experienced high burnout. There was a relationship and as risk factor in the organizational support variable (POR=4.426; 95%CI 2.028 - 9.662). However, as protective factors in gender variable (POR=0.324; 95%CI=0.117 - 0.898) and job demands (POR=0.283; 95%CI 0.132 - 0.610) on the incidence of burnout in PT X production workers. To reduce the risk of burnout, PT X necessary to provide counselling facilities, work rotation system, increase appreciation and communication between colleagues and supervisor.